Calcium signaling and cell cycle: Progression or death. (March 2018) - Humeau, Juliette; Bravo-San Pedro, José Manuel; Vitale, Ilio; Nuñez, Lucia; Villalobos, Carlos; Kroemer, Guido; Senovilla, Laura
Graphical abstract: Highlights: Ca 2+ regulates cell cycle proliferation and cell death mainly through the Ca 2+ /calmodulin complex. Ca 2+ participates in the control of the cell cycle through three checkpoints. Alterations in all these processes may lead to cell cycle arrest and apoptosis. Malignant transformation is accompanied by changes in Ca 2+ homeostasis that cause dysfunctions in the signs of proliferation and/or death. Cancer cells can be selectively killed and/or arrested by targeting Ca 2+ channels. Abstract: Cytosolic Ca 2+ concentration levels fluctuate in an ordered manner along the cell cycle, in line with the fact that Ca 2+ is involved in the regulation of cell proliferation. Cell proliferation should be an error-free process, yet is endangered by mistakes. In fact, a complex network of proteins ensures that cell cycle does not progress until the previous phase has been successfully completed. Occasionally, errors occur during the cell cycle leading to cell cycle arrest. If the error is severe, and the cell cycle checkpoints work perfectly, this results into cellular demise by activation of apoptotic or non-apoptotic cell death programs. Cancer is characterized by deregulated proliferation and resistance against cell death. Ca 2+ is a central key to these phenomena as it modulates signaling pathways that control oncogenesis and cancer progression. Here, we discuss how Ca 2+ participates in the exogenous and endogenous signals controlling cell proliferation, as well as in the mechanisms by which cells die if irreparable cell cycle damage occurs. Moreover, we summarize how Ca 2+ homeostasis remodeling observed in cancer cells contributes to deregulated cell proliferation and resistance to cell death. Finally, we discuss the possibility to target specific components of Ca 2+ signal pathways to obtain cytostatic or cytotoxic effects.